2021
DOI: 10.1371/journal.pone.0256652
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and health-related quality of life of patients with microtia following reconstructive surgery using the Nagata technique

Abstract: Objective This study aimed to investigate the functional outcomes, satisfaction, and quality of life of patients with microtia following reconstructive surgery. Methods This cross-sectional study was conducted using retrospective data of patients with microtia following reconstructive surgery using the Nagata technique. Data were obtained from the medical records of patients who underwent reconstructive surgery at the Division of Facial Plastic and Reconstructive Surgery, Department of Otorhinolaryngology, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Some subsequently undergo several surgical interventions 36 . This compares with individuals with auricle anomalies reconstruction who report favourable quality of life outcomes for various techniques, which usually require only one or two stages 37 . The overall well‐being of individuals after reconstruction for auricle anomalies can be related to better academic achievements, as reported in numerous previous studies 38 .…”
Section: Discussionmentioning
confidence: 86%
“…Some subsequently undergo several surgical interventions 36 . This compares with individuals with auricle anomalies reconstruction who report favourable quality of life outcomes for various techniques, which usually require only one or two stages 37 . The overall well‐being of individuals after reconstruction for auricle anomalies can be related to better academic achievements, as reported in numerous previous studies 38 .…”
Section: Discussionmentioning
confidence: 86%
“…After screening titles for relevancy to the topic, 88 articles remained. Twelve of those studies met the inclusion criteria 3–14 . Four studies utilized the Brent method of repair with inclusion of 563 ear reconstructions.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of those studies met the inclusion criteria. [3][4][5][6][7][8][9][10][11][12][13][14] Four studies utilized the Brent method of repair with inclusion of 563 ear reconstructions. Nine studies implemented the Nagata technique in 2304 reconstructions.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature search, no study comparing the quality of life between patients receiving autologous and alloplastic reconstruction. Some have studied the quality-of-life following ear reconstruction using a certain technique, such as Widodo et al 6 who found many patients have good health-related quality of life (HRQoL) after ear reconstruction using the Nagata technique (autologous) and Braun et al 11 who found that alloplastic reconstruction using MedPor® significantly increase patient's HRQoL. These findings are supported by a systematic review stating that both autologous and alloplastic reconstruction has good outcomes in HRQoL.…”
Section: Discussionmentioning
confidence: 95%
“…The questions evaluate the aesthetic outcomes, functional outcomes, psychosocial outcomes, and clinic-related outcomes. 6,7 This paper aims to discover through literature whether autologous or alloplastic material is a better choice for auricular reconstruction.…”
Section: Introductionmentioning
confidence: 99%